HLA Antigens and Factor VIII Antibody in Classic Hemophilia - Frommel, D; Allain, J P; Saint-Paul, E; Bosser, C; Noël, B; Mannucci, P M; Pannicucci, F; Blombäck, M; Prou-Wartelle, O; Muller, J Y (Thrombosis and Haemostasis, 1981)
Possible interrelations between the immune response factor VIII and the major histocompatibility system were investigated in 57 multi-transfused hemophilic brothers belonging to 26 families. Linkage appears very unlikely although formal proof of independence cannot be offered. The HLA system, therefore, does not provide markers predictive for the development of antibodies to factor VIII in severe hemophilia A.
Keywords: Hemophilia; HLA antigens; Factor VIII antibody; Immunogenetics; Specific immune responsiveness